(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Introduction: Juvenile nasopharyngeal angiofibroma is a pathologically benign yet locally aggressive and destructive vascular tumor. It comprises 0.5% of neoplasms in the head and neck typically affecting adolescent boys. Material & Method: A retrospective study of surgically treated patients of juvenile nasopharyngeal angiofibroma was performed over a period of 3 years. The study discusses about most common presenting complaints, correlation of preoperative radiological and intraoperative staging and factors affecting recurrence of juvenile nasopharyngeal angiofibroma. Result: 20 surgically treated patients were included in the study; all were male with average age of 15.7yrs having epistaxis and nasal obstruction as the most common symptom. Preoperative staging was almost similar with intraoperative staging except one case which needed upstaging. Suitable surgical approach was adopted considering site of lesion. Two recurrent cases were also managd successfully. Conclusion: Juvenile nasopharyngeal angiofibroma is a benign disease of male adolescents with bone eroding capacity. The planning of surgical approach for its excision has utmost importance which is based on extent of the lesion or staging done pre-operatively. Early preoperative evaluation not only helps in better management but also prevents recurrence of JNA. Bangladesh J Otorhinolaryngol; April 2015; 21(1): 33-37